ApoE isoform-dependent effects of xanthohumol on high fat diet-induced cognitive impairments and hippocampal metabolic pathways - Kundu, Payel; Holden, Sarah; Paraiso, Ines L.; Sudhakar, Reetesh; McQuesten, Chloe; Choi, Jaewoo; Miranda, Cristobal L.; Maier, Claudia S.; Bobe, Gerd; Stevens, Jan F.; Raber, Jacob (Frontiers in Pharmacology, 2022)
Consumption of a high fat diet (HFD) is linked to metabolic syndrome and cognitive impairments. This is exacerbated in age-related cognitive decline (ACD) and in individuals with a genetic risk for Alzheimer’s disease (AD). Apolipoprotein E (apoE) is involved in cholesterol metabolism. In humans, there are three major isoforms, E2, E3, and E4. Compared to E3, E4 increases ACD and AD risk and vulnerability to the deleterious cognitive effects of a HFD. The plant compound Xanthohumol (XN) has beneficial effects on cognition and metabolism in C57BL/6J (WT) male mice put on a HFD at 9 weeks of age for 13 weeks. As the effects of XN in the context of a HFD in older WT, E3, and E4 female and male mice are not known, male and female WT, E3, and E4 mice were fed a HFD alone or a HFD supplemented with 0.07% XN for 10 or 19 weeks, starting at 6 months of age, prior to the beginning of behavioral and cognitive testing. XN showed sex- and ApoE isoform-dependent effects on cognitive performance. XN-treated E4 and WT, but not E3, mice had higher glucose transporter protein levels in the hippocampus and cortex than HFD-treated mice. E3 and E4 mice had higher glucose transporter protein levels in the hippocampus and lower glucose transporter protein levels cortex than WT mice. In the short-term experiment, hippocampal sphingolipid analysis revealed that E4 mice had nearly double as high ceramide and sphingomyelin levels than E3 mice and that male mice had higher level of glycosylated ceramide than female mice. When the differential effects of HFD in E3 and E4 males were assessed, the arginine and proline metabolism pathway was affected. In the extended exposure experiment, in E3 males XN treatment affected the arginine and proline metabolism and the glycine, serine, and threonine metabolism. Myristic acid levels were decreased in XN-treated E3 males but not E3 females. These data support the therapeutic potential for XN to ameliorate HFD-induced cognitive impairments and highlight the importance of considering sex and ApoE isoform in determining who might most benefit from this dietary supplement.